Korelasi Penghargaan Kendiri dan Tingkah laku Kerohanian Remaja Asnaf - Siti Jamiaah Abdul Jalil; Ahmad Irdha Mokhtar; Fariza Md. Sham; A'dawiyah Ismail; Farah Ayuni Mohd Hatta; Anuar Puteh; Abdul Razaq Ahmad; Safiah Abd Razak; Asmadi Abdul Rahman; Wafa Amni Fajuri (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah, Volume 36 issue 02 Page (166–178)